Pemberdayaan Remaja melalui Pelatihan Duta Gizi dan Peer Education sebagai Upaya Pencegahan Prediabetes di SMK Muhammadiyah 1 Weleri - Triya Ulva Kusuma; Nafilah Nafilah; Radiati Moviana; Mohamad Zaenal Arif; Alvina Ayu Karmila; Annisa’ Nur Makarimah (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The phenomenon of prediabetes is increasingly being found in adolescents. Prediabetes in adolescents can cause various negative impacts both in the short and long term. Limited knowledge regarding nutrition and high consumption of sugary drinks are strongly related to the high number of prediabetes cases among adolescents. This community service activity aims to increase the knowledge and capacity of adolescents through empowering adolescent nutrition ambassadors and peer education in prediabetes prevention efforts. The activity was carried out at SMK Muhammadiyah 1 Weleri in two forms: intensive training for 8 adolescent nutrition ambassadors, and peer education by adolescent nutrition ambassadors to 78 other students using interactive educational methods, simulations, demonstrations, practice, and discussions. Evaluation was carried out through pre-tests and post-tests in each session. The results showed that there was an increase in adolescent knowledge and skills after the activity. The conclusion of this activity is that adolescent empowerment through intensive nutrition ambassador training and peer education is effective in increasing adolescent knowledge and skills as a strategy for preventing prediabetes.